Understanding the history of a volcanic arc: linking geochemistry of Cenozoic volcanic cobbles from the Wrangell arc, Alaska, to upper plate and subducting slab tectonic processes - Morter, Bethany Kathleen (Kansas State University, 2017)
The Wrangell arc (WA) is a ~29 Ma magmatic belt, extending from south-central Alaska into the Yukon Territory, that lies above the edges and leading front of the Yakutat microplate, a buoyant oceanic plateau that is causing shallow subduction (11-16º) in the region. The WA occurs in a transition zone between “normal” Aleutian subduction to the west and dextral strike-slip tectonics to the east, accomplished by the Totschunda, Denali, and Duke River faults. This geologic setting offers a chance to study the interrelations between subduction, strike-slip motion, and slab-edge magmatic processes in a relatively well-exposed arc. We implemented a novel technique of applying geochemical and geochronologic analyses on volcanic cobbles collected from glacio-fluvial systems (rivers, streams, and glaciers) encircling/draining the WA. Our primary objective is to integrate our cobble datasets with the existing bedrock and detrital sand records to develop a comprehensive understanding of WA magmatism through time and space. Our secondary objective is to test the validity of this novel technique for reproducing what is documented from bedrock samples and its potential for utilization in other locations. This study provides new major element data from 215 samples and trace element data from 236 samples collected from 17 major rivers that drain from the modern western and central WA (this study excludes the eastern WA). This study also provides new age data from a total of 119 samples from 10 major rivers. New geochronology of modern detrital volcanic cobbles and sand/zircons reveal that the WA initiated at ~29 Ma and that magmatism migrated northwestward through time. Cobble ages and locations across the arc agree with the northwestward progression of magmatism previously identified by Richter et al. (1990). Forty-seven cobbles are dated <~1 Ma and only nine cobbles are dated 29 – ~20 Ma, whereas there are no cobbles from 17 – ~13 Ma. Geochemical data reveal similarities between our data and that of the <~5 Ma WA defined by Preece and Hart (2004): Trend 1 (transitional-tholeiitic), Trend 2a (calc-alkaline), Trend 2b (calc-alkaline, adakite-like). Therefore, we use the geochemical framework defined in Preece and Hart (2004) to contextualize spatio-temporal trends of magmatism and tectonic implications in the WA during its ~29 m.y. history. Trend 2a and 2b cobbles are spatially and temporally ubiquitous in the WA, indicating that subduction and partial slab melting have been the dominant tectonic processes throughout WA history. Trend 1 cobbles are not found in southwestern WA rivers and are temporally restricted to ~11 – ~6 Ma and <1 Ma, suggesting intra-arc extension has occurred in discrete periods during WA history. These conclusions are confirmed by the existing (Richter et al., 1990; Skulski et al., 1991; 1992; Preece and Hart, 2004; Trop et al., 2012) and new (Berkelhammer, 2017; Weber et al., 2017) bedrock records. Finally, this study shows that the sampled cobble lithologies largely reproduce the known bedrock record in geochemical, temporal, and spatial contexts, which suggests the novel methodology applied here can be used in other locations where field conditions limit access to bedrock.
Keywords: Cobble; GeochemistryWrangell arc